2007
DOI: 10.1021/jp073198j
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of LNA:DNA Hybrids from Molecular Dynamics Simulations:  The Effect of Locked Nucleotides

Abstract: Locked nucleic acids (LNAs) exhibit a modified sugar fragment that is restrained to the C3'-endo conformation. LNA-containing duplexes are rather stable and have a more rigid structure than DNA duplexes, with a propensity for A-conformation of the double helix. To gain detailed insight into the local structure of LNA-modified DNA oligomers (as a foundation for subsequent exploration of the electron-transfer capabilities of such modified duplexes), we carried out molecular dynamics simulations on a set of LNA:D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 70 publications
(171 reference statements)
6
42
1
1
Order By: Relevance
“…24 In the absence of reliable NMR structures, molecular dynamics simulations provide the best source of information about structure. 19 Ivanova et al have suggested on the basis of such simulations that it should be possible to design a sequence with a high propensity for hole transfer along an LNA-modified helix. 17 Our A 2 L G n diblock hairpins that have values of Φ cs and τ cs that are only slightly smaller than those for their all-DNA analogues (Table 1) provide an approach to this objective.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In the absence of reliable NMR structures, molecular dynamics simulations provide the best source of information about structure. 19 Ivanova et al have suggested on the basis of such simulations that it should be possible to design a sequence with a high propensity for hole transfer along an LNA-modified helix. 17 Our A 2 L G n diblock hairpins that have values of Φ cs and τ cs that are only slightly smaller than those for their all-DNA analogues (Table 1) provide an approach to this objective.…”
Section: ■ Concluding Remarksmentioning
confidence: 99%
“…24 The minimized structures for LNA:DNA and LNA:RNA duplexes have nonlinear helical axes; 19,24 hence, it is unlikely that the two stilbenes in a LNA:DNA hairpin are approximately parallel to each other as they are in the B-DNA capped hairpin ( Figure 5). Thus, the sign and amplitude of the stilbene EC-CD spectra in the LNA:DNA hybrids cannot be simply correlated with the dihedral angle between the stilbene electronic transition dipole moments, as is possible for the B-DNA hairpins.…”
mentioning
confidence: 99%
“…The effects of locked nucleotides on backbone flexibility and base stacking may render mismatches in the direct vicinity of LNAs refractory to recognition by MMR proteins. LNA nucleotides are confined to the 3′-endo conformation and induce a shift in sugar puckering toward this conformation of directly neighboring nucleotides, which is most pronounced at the 3′ side (46,47). Thus, LNAs near a mismatch may prohibit the bending of the DNA that is required for stabilization of the MutS-DNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on DNA have been focused on two aspects: structure-based function prediction and DNA-drug/ligand complex interaction. The MD simulation method provides a lot of detailed information that helps to elucidate the structure, thermodynamics, and kinetics of the native, modified, and complexed nucleic acid for rational drug design [31][32][33] [42], modified backbones [43,44], modified bases [45,46], antisense oligonucleotides [47,48], and damaged DNA [49,50], as well as DNA/RNA hybrid [51].…”
Section: Simulations Of Dnamentioning
confidence: 99%
“…Ivanova et al . reported the unrestrained MD simulations[65] on a series of LNA-incorporated DNA 9-mer duplexes whose structural information was available via NMR experiments.…”
mentioning
confidence: 99%